NLP for Project Managers : Make things happen with neuro-linguistic programming. - Parkes, Peter (British Informatics Society, 2011)
Project management is becoming less about managing tools and processes and more about delivering through people. This is the only book on Neurolinguistic Programming written specifically for project managers. It will equip them to communicate across cultures, resolve conflicts, motivate teams and become better leaders.